Does Israel want peace? - Ahsan, Abdullahil (TurkeyAgenda, 2014)
I read Gideon Levy’s article “Israel does not want peace” in Haaretz (04.07.14) with immense interest. I used to read Haaretz almost regularly until a few years ago but recently I lost interest in it. A number of friends drew my attention to Levy’s article and I found it attractive because it states a fact that I have come to believe years ago. But to hear this from an Israeli journalist is admiring. I also appreciate Haaretz’s courage to publish it. I am not sure whether any other Israeli or Western newspaper would have the courage to publish such an article. This reminds me of Mearsheimer and Walt’s The Israel Lobby for which the senior American academics had to look for publisher around the world. Levy’s short and precise thesis is much more direct and revealing than The Israel Lobby. Does this mean we are at cul-de-sac? Is there no hope for peace? I don’t think so. I shall explain why. But before I explain why I hold the view that rays of hope has not absolutely vanished, I shall give my view why I believe Israel does not want peace..........